An analytical study of the change in some biomechanical indicators of steeplechase (1-2-7-8) in the 400m steeplechase for elite runners under 20 years old - Lami, M.; Ajeel, A. (International Journal of Disabilities Sports and Health Sciences, 2024)
The aim of this study is to analyze the changes in the values of some biomechanical indicators (1- 2- 7-8) of steeplechase in the 400m steeplechase for elite runners under the age of 20. In this study, 8 athletes (age: 19.2 ± 0.98; height: 1.87 ± 0.05) were analyzed in the men's 400 m steeplechase. Analysis of variance test was used to compare differences between male athletes in terms of independent variables; significance was set at p < 0.05. As Result; the distance before the hurdle that, there is a non-significant value between the first hurdle and the second hurdle (p>0.701). As for the distance variable after the barrier, it turns out that there are significant differences in the first And the seventh, eighth (sig to Hurdle 1, p<0.013; p<0.003). As for the variable of the height of the body's center of gravity, the differences were not significant between the first and second and in the seventh And the eighth hurdles (p>0.141; p>0.256 ). But, We identified significant differences between other hurdles groups. As for the angle tangent variable, the results appeared significant for all the differences between the hurdles except for the difference between the seventh and the eighth barrier. In Conclusion, it is recommended to focus on training physical abilities according to performance and within bends, to train to maintain running rhythm, and to focus on speed and endurance exercises.